Configuring thermal ablation volumes for treatment of distinct tumor shapes: a repeatability study using a robotic approach - Bulatović, Milica; Hermann, Jan; Tinguely, Pascale; Paolucci, Iwan; Weber, Stefan (Frontiers in Oncology, 2024)
ObjectivesIn the current clinical practice of thermal ablation treatment for liver tumors, achieving consistent and effective clinical outcomes across tumors of varying shapes, sizes and locations remains challenging. The aim of this study was to evaluate the repeatability of a novel robotic approach for configurable ablation of distinct tumor shapes and compare it to the standard ablation technique for creating ellipsoidal ablation volumes.Materials and methodsThe repeatability was evaluated in terms of width variability in created ablation volumes. Using a robotic navigation platform, custom ablation profiles configured with power, time, and distance parameters were designed to create four distinct ablation shapes. The profiles were applied for microwave ablation in a tissue-mimicking liver model. For comparison of ablation shape variability, six standard ellipsoidal shapes were created using the standard ablation technique by configuring power and time parameters. For each sample, the resulting ablation area was segmented, and the resulting shape width and length were calculated at the measurement points. Width variability was calculated as the median of the absolute pairwise differences in width at each measurement point, and configurable versus standard ablation shapes were compared using the Mann–Whitney U test.ResultsAll tissue-mimicking samples were successfully ablated using both configurable (n = 48) and standard ablation technique (n = 35). Study findings revealed noninferiority regarding repeatability of created ablation shapes using the robotic platform for configurable ablation, compared to created standard ellipsoidal ablation shapes (p < 0.001, 95% CI ≤ -0.05 mm, Δ = -0.22 mm). Median repeatability of created configurable shapes was 1.00 mm, and for standard shapes 1.22 mm. Maximal repeatability for both groups was below 3 mm.ConclusionThe repeatability of configurable ablation shapes was observed to be noninferior to the standard ablation shapes. Achieving configurable ablation volumes underscores the potential to advance personalization of thermal ablation treatment and broaden its applicability to distinct tumor cases. In-vivo validation is needed for evaluation of the clinical implications of this novel treatment technique.